2001
DOI: 10.1001/archpsyc.58.5.485
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Double-blind Comparison of Sertraline and Placebo in the Treatment of Posttraumatic Stress Disorder

Abstract: The results of the current study suggest that sertraline is a safe, well-tolerated, and significantly effective treatment for PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
208
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 415 publications
(223 citation statements)
references
References 43 publications
10
208
2
3
Order By: Relevance
“…Recommendations in the Society for Traumatic Stress Studies guidelines (Benedek et al, 2009;Foa, Keane, and Friedman, 1999) and the American Psychiatric Association guidelines (American Psychiatric Association, 2004) also support the measure. Randomized controlled trials and meta-analyses of the results of those trials support the use of an SSRI/SNRI as a first-line agent for the treatment of PTSD (Brady et al, 2000;Davidson, Rothbaum, et al, 2001;Foa, Davidson, and Frances, 1999;Jonas et al, 2013;Stein, Ipser, and Seedat, 2009), as does a recent IOM report (Institute of Medicine, 2012). (For more detail, see Appendix A.…”
Section: Quality Measure Results For Ptsd Measure Overviewmentioning
confidence: 83%
See 1 more Smart Citation
“…Recommendations in the Society for Traumatic Stress Studies guidelines (Benedek et al, 2009;Foa, Keane, and Friedman, 1999) and the American Psychiatric Association guidelines (American Psychiatric Association, 2004) also support the measure. Randomized controlled trials and meta-analyses of the results of those trials support the use of an SSRI/SNRI as a first-line agent for the treatment of PTSD (Brady et al, 2000;Davidson, Rothbaum, et al, 2001;Foa, Davidson, and Frances, 1999;Jonas et al, 2013;Stein, Ipser, and Seedat, 2009), as does a recent IOM report (Institute of Medicine, 2012). (For more detail, see Appendix A.…”
Section: Quality Measure Results For Ptsd Measure Overviewmentioning
confidence: 83%
“…Empirical support, from randomized control trials and meta analyses of those trials, exists to justify the use of SSRIs and SNRIs as a first-line agent for the treatment of PTSD (Brady et al, 2000;Davidson, Rothbaum, et al, 2001;Foa, Davidson, and Frances, 1999;Jonas et al, 2013;Stein, Ipser, and Seedat, 2009). A recent review of PTSD pharmacotherapy indicated that the largest and greatest number of trials showing efficacy have been with the SSRIs (Ipser and Stein, 2012).…”
Section: Research Evidencementioning
confidence: 99%
“…The SSRIs are the most commonly prescribed medication for the treatment of PTSD. Large RCTs conducted with sertraline (Brady et al [78], Davidson et al [79]) and paroxetine (Marshall et al [80]) resulted in U.S. Food and Drug Administration approval for their use with PTSD. The effect size for overall symptom relief is modest, d = 0.3-0.4.…”
Section: Antidepressant Agentsmentioning
confidence: 99%
“…The more recent, and also more successful, studies (Brady et al, 2000;Connor et al, 1999;Davidson et al, 2001b;Marshall et al, 2001;Martenyi et al, 2002b;Tucker et al, 2001;van der Kolk et al, 1994) have focused on more general trauma samples that included both men and women with predominately noncombat traumas and have utilized serotonin reuptake inhibitors. Below we describe the major treatments for chronic PTSD that have received empirical support.…”
Section: Interventions For Individuals With Chronic Ptsdmentioning
confidence: 99%
“…Since 1994, three SSRI medications have been shown to be more effective than placebo in the treatment of PTSD: fluoxetine (Connor et al, 1999;Martenyi et al, 2002b;van der Kolk et al, 1994), sertraline (Brady et al, 2000;Davidson et al, 2001b), and paroxetine (Marshall et al, 2001;Tucker et al, 2001). The latter two medications have received the FDA indication for treatment of PTSD.…”
Section: Medicationmentioning
confidence: 99%